Analisis Kualitas Daya Listrik Pada Penggunaan Modul Surya Sederhana Untuk Pompa Air Rumah Tangga - Syarif Hidayat Hidayat (Sekolah Tinggi Teknik - PLN, 2021)
The use of solar modules to meet the needs of everyday life is something interesting to use. Harmonics is a phenomenon of power quality deviation that can distort voltage and current waveforms. In this experiment, a simple inverter with 1000 W capability will be used, then will be loaded with water pumps and other household appliances. The method used is to measure the power factor and harmonics generated by using a measuring device. In this process needs to be assessed and will be seen using the ability of the inverter and the quality of the electric power generated in this solar power generation system. Based on the results of measurements and calculations on a water pump with a power of 680 W and 1 incandescent lamp with a power of 60 Watts, the value of the power factor generated is 0.95 while the total harmonic voltage distortion (THDv) value is when the water pump load is THDv 1.9 % and at THDv incandescent lamps 1.6%.